Stress Management Among Adolescents: A Study in Boarding Schools of Kathmandu - Adhikari, Dinesh (NPRC Journal of Multidisciplinary Research, 2025)
Background: Adolescence is a critical developmental stage marked by heightened vulnerability to stress, particularly in boarding school environments where academic pressures, social adjustments, and separation from family converge. In Nepal, psychosocial dysfunction affects approximately 17% of adolescents, with stress linked to anxiety, depression, and impaired academic performance 215. Despite growing recognition of this issue, limited research has focused on stress management among boarding school adolescents in Kathmandu, where unique institutional demands exacerbate stressors. Objective: This study aimed to (1) assess the prevalence of stress among adolescents in Kathmandu’s boarding schools, (2) identify key stressors (academic, relational, environmental, and personal), (3) evaluate gender and age differences in stress levels, and (4) explore existing coping strategies to inform targeted interventions. Method: A descriptive cross-sectional design was employed, using Sheldon Cohen’s Perceived Stress Scale to survey 100 adolescents (45 female, 55 male) aged 13–18 from two boarding schools in Kathmandu. Bivariate analysis examined associations between stress levels and demographic/contextual factors. Findings: Moderate to high stress levels were prevalent (85% of respondents), with females and older adolescents reporting higher stress. Primary stressors included academic performance (e.g., low grades), peer conflicts, future uncertainty, and disrupted sleep patterns. Gender disparities were notable, with females more likely to experience high stress (22.2% vs. 18.2% of males). Only 15% of students reported low stress, underscoring the widespread burden. Conclusion: The study highlights an urgent need for institutional stress management strategies, such as school-based counseling, structured wellness programs, and extracurricular activities, to mitigate the adverse effects of stress on mental health and academic outcomes. Novelty: This research contributes localized insights into stress dynamics in Nepali boarding schools, emphasizing the interplay of cultural, academic, and environmental factors. It advances prior work by identifying specific, actionable stressors in this understudied setting 1015.